2015
DOI: 10.5935/1806-0013.20150020
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and musculoskeletal complaints among elite athletes of Santa Catarina

Abstract: BACKGROUND AND OBJECTIVES: There are many physiological processes going on during sleep which are important for physical and emotional balance and especially for motor function, essential for athletes' performance. This study aimed at investigating associations between sleep duration and quality and musculoskeletal complaints among elite athletes of the state of Santa Catarina. METHODS: Four hundred and fifty-two athletes from various sports have been investigated on issues related to sleep (duration, quality)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
10
2
Order By: Relevance
“…This assumption is supported by the prevalence rates reported, with levels of significant sleep disturbance ranging from 38% of multi-sport athletes [64] to 57% of bobsleigh competitors [1]. The more conservative PSQI threshold of >8, indicative of highly disturbed sleep, also showed a relatively high prevalence, ranging from 22 to 26% [1, 63].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This assumption is supported by the prevalence rates reported, with levels of significant sleep disturbance ranging from 38% of multi-sport athletes [64] to 57% of bobsleigh competitors [1]. The more conservative PSQI threshold of >8, indicative of highly disturbed sleep, also showed a relatively high prevalence, ranging from 22 to 26% [1, 63].…”
Section: Resultsmentioning
confidence: 77%
“…Formal (PSQI) assessments of sleep quality suggest similarly high levels of insomnia-type symptoms (Table 4 ), with mean values at [ 64 ] or above the threshold of >5 [ 1 , 62 , 63 , 65 , 70 ]. This assumption is supported by the prevalence rates reported, with levels of significant sleep disturbance ranging from 38% of multi-sport athletes [ 64 ] to 57% of bobsleigh competitors [ 1 ]. The more conservative PSQI threshold of >8, indicative of highly disturbed sleep, also showed a relatively high prevalence, ranging from 22 to 26% [ 1 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the quantity and quality of sleep, Kent et al [ 15 ] showed that a social isolation routine could lead to sleep disorders, anxiety, and depression. Sleep quality has huge importance for athletes, since it enables maintained alertness, contributes to a shorter reaction time, and improves mood and physical vigor [ 20 , 36 ]. Furthermore, Rowlands et al [ 37 ] used data from 91,248 UK Biobank participants with accelerometer data and demonstrated an association between markers of sleep/rest and physical activity and the risk or severity of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Nationally, it has been pointed out that 48.5% of young athletes sleep less than 8 hours a day, with prevalence of low sleep quality of 41.7%. 9 …”
Section: Introductionmentioning
confidence: 99%